The Relationship Between Giving Lime And Honey To Reduce Nausea And Vomoting In Pregnant Women In The First Trimester At The Sarfina Sembiring Clinic In 2025 - Nova Prihartini; Agusanna Dewi Silangit (Universitas Muhammadiyah Palu, 2026)
Nausea and vomiting are obstetric problems that are common in 50-80% of pregnant women during the first trimester which begins in the morning and often continues throughout the day. According to the results of the study, the incidence of nausea and vomiting in the world is estimated to be 70-80% of the number of pregnant women. Lime contains vitamin C, flavonoids, and vitamin B6 which can help reduce nausea and vomiting in pregnant women and honey can help maintain stamina and health during pregnancy. This study aims to find out the relationship between giving lime and honey to reduce nausea and vomiting in pregnant women in the first trimester at the Pratama Sarfina clinic in 2025. The population of this study is pregnant women with nausea and vomiting at the Pratama Sarfina Clinic, the sample in this study is 15 pregnant women in the first trimester with nausea and vomiting. The sampling technique is accidental sampling. The type used is in the form of primary data, namely data obtained directly from respondents, the characteristics of respondents are age, parity, education, and occupation. The results of the Chi-Square test research have a value of Sig?0.05=0.000, then Ho is rejected and Ha is accepted, this shows that there is a relationship between giving lime and honey with a decrease in nausea and vomiting in pregnant women in the first trimester.